Photosensitive field effect transistor based on metallo-phthalocyanines containing (4-pentylphenyl) ethynyl moieties - Yenilmez, H. Yasemin; Sahin, Ayse Nur; Altindal, Ahmet; Bayir, Zehra Altuntas (ELSEVIER SCIENCE SA, 2021)
The syntheses of new cobalt, manganese and zinc phthalocyanine complexes containing 4-pentylphenylethynyl substituents at the peripheral positions are reported. 4-[(4-pentylphenyl) ethynyl] phthalonitrile was obtained through Sonogashira coupling reaction. The new compounds have been characterized using UV-vis, FT- IR, H-1 NMR, C-13 NMR, and mass spectroscopy data. In order to study the dependence of device performance on the central metal atom, photosensitive field effect transistor based on tetra-substituted metallo phthalocyanines with [(4-pentylphenyl) ethynyl groups at peripheral positions were fabricated and characterized. Photoelectric characterization results showed that the device with active layer of 3 exhibits highest photoelectric performance with maximum field effect mobility (4.27 x10(3) cm(2)/Vs), photosensitivity (72.05), and photo/dark current ratio (230). It was found that the photoelectric performance of the Pc compounds depends on the central metal atom which is found consistent with UV-vis spectrum. Surface topography of the sensing films were analyzed by atomic force microscopy.
Keywords: 1-Ethynyl-4-pentylbenzene; Phthalocyanine; Sonogashira-coupling; Photo responsive field effect transistor; Photosensitivity; Materials Science; Physics; Polymer Science